Synthesis of isoflavene-thiosemicarbazone hybrids and evaluation of their anti-tumor activity. Issue 11 (1st June 2017) - Yee, Eugene M.H.; Brandl, Miriam B.; Black, David StC; Vittorio, Orazio; Kumar, Naresh
Graphical abstract: Abstract: Phenoxodiol is an isoflavene with potent anti-tumor activity. In this study, a series of novel mono- and di-substituted phenoxodiol-thiosemicarbazone hybrids were synthesized via the condensation reaction between phenoxodiol with thiosemicarbazides. The in vitro anti-proliferative activities of the hybrids were evaluated against the neuroblastoma SKN-BE(2)C, the triple negative breast cancer MDA-MB-231, and the glioblastoma U87 cancer cell lines. The mono-substituted hybrids exhibited potent anti-proliferative activity against all three cancer cell lines, while the di-substituted hybrids were less active. Selected mono-substituted hybrids were further investigated for their cytotoxicity against normal MRC-5 human lung fibroblast cells, which identified two hybrids with superior selectivity for cancer cells over normal cells as compared to phenoxodiol. This suggests that mono-substituted phenoxodiol-thiosemicarbazone hybrids have promising potential for further development as anti-cancer agents.